Smallholder farmers’ perception on ecosystem-based approaches for remedying land degradation in Nabdam District, Ghana - Humphrey Anafo; Kenneth Peprah; Francis Issahaku Malongza Bukari (Journal of Degraded and Mining Lands Management, 2020)
The co-benefits from the implementation of ecosystem-based approaches in managing land degradation and enhancing ecosystem services have not been adequately explored in the mainstream literature. The study aims at identifying the indicators of land degradation and the associated ecosystem-based approaches used to remedy the situation. The ecosystem-based approaches refer to ecosystems and ecosystem services together with their flexible management in a cultural setting. The paper adopts a descriptive research design with quantitative and qualitative approaches. Principally, it targets 236 smallholder farmers for the survey, key informants for interviews and community members for focus group discussion. The results revealed that land degradation is mainly identified by reduced crop yield (53%). Farmer identification of land degradation is influenced by the age of the farmer (p = 0.001) with  The ecosystem-based approaches include stone bonding, crop rotation, mulching and particularly, composting (53%). The ecosystem-based approaches are statistically linked to the communities with p-value of 0.020. A p-value of 0.001 shows that the ecosystem-based approaches are beneficial in the various study communities. Farmers’ experience over the past five years is statistically related to the age of respondents (p = 0.008). The p-value of 0.000 indicates very strong statistical significance of the challenges of ecosystem-based approaches in the communities. The ecosystem-based approaches have long term goals for sustainable land improvement and may not be realized unless there is direct policy to take care of the approaches even in the short term.